Availability, Use and Challenges of Information and Communication Technology Gadgets in Sustainable Small Scale Dairy Farmers Livelihoods in Nandi County, Kenya - Beru, M. K.; Cheserek, G. Cheserek; Kiptui, M. (Africa Environmental Review Journal, 2018)
Information and Communication Technology (ICT) gadgets are vital for the enhancement of sustainable small scale dairy farmers’ livelihoods in less developed countries. Therefore, its availability and use is quite critical in enabling farmers acquire relevant dairy farming information through ICT integration in dairy farming extension services. Dairy farming communities appreciate ICT gadgets as easy, fast and convenient way to communicate and get prompt answers of respective dairy farming problems. In Kenya dairy farming contributes to 14% of agricultural GDP and 3.5% of total GDP of the economy. It also contributes to food stability, provision of employment opportunities and livelihoods. In order to fight food insecurity and enhance livelihoods, sustainable agriculture is paramount. The use of ICT gadgets to acquire dairy farming information is significant given that the ratio of extension officers to farmers is 1:1200 as opposed to Food and Agricultural Organization (FAO) recommendation of 1: 400. Thus, this paper looks at availability and use of ICT gadgets in enhancing sustainable small scale dairy farmers’ livelihoods in Nandi County, Kenya.